HUBUNGAN MOTIVASI BELAJAR DENGAN HASIL BELAJAR IPA DI SEKOLAH DASAR - Lativani, Lativani; Arlis, Syamsu; Masniladevi, Maniladevi (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2014)
This study aims to determine whether there is a positive and significant relationship between learning motivation with science learning outcomes in grade V SDN Gugus Nagari Andiang. This research is a quantitative research with correlational research type. Sampling data is taken by Total Sampling technique. The sample of this study amounted to 38 people with a population of 38 people as well. The instrument used is a questionnaire with multiple choice form. The result showed that rhitung> rtabel is 0,619 > 0,3202 with α = 0,05 which means H0 is rejected. So the motivation to learn has a relationship with the results of science learning grade V SDN Gugus Nagari Andiang District Suliki District 50 Kota.             Keywords: learning motivation, science learning outcomes